Internalisasi Wawasan Moderasi Beragama di Kalangan Pemuda melalui Media Sosial - Fadlillah, Fadlillah; Faruq, Dukan Jauhari; Mutmainah, Siti; Alvatun Ni'mah, Akhsani (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
Along with the development of the times, existing technology is increasingly experiences innovation and progress very rapidly. This form of technological development gave birth of interesting phenomena in people’s lives, for example the widespread use of social media, which is commonly referred to as the digital era. It provides various things that human need, such as entertainment, service, and literacy. However, social media as a form of digitalization presents religious naratives with free access, often used by certain groups to cause conflict and identity political goals which have an impact on the degradation of religious tolerance. Youth as generation hase a role in emphasizing such counter- narratives trough efforts to internalize religious moderation insights trough contents on social media as strengthening of peace.